Pengembangan Elektronik Modul Berbasis Contextual Teaching and Learning pada Materi Larutan Elektrolit dan Non Elektrolit untuk SMA/MA - Rini Puspita Sari; Andromeda Andromeda (Universitas Negeri Padang, 2022)
Most of the topics discussed in chemistry are abstract, meaning that the concepts studied do not appear concrete. E-modules are learning media that can be presented using multiple chemical presentations to present abstract material, one of which is electrolyte and non-electrolyte solution material. The aim of this research is to produce a valid e-module of electrolyte and non-electrolyte solutions based on contextual teaching and learning. The validity value will be obtained by using the Aiken’s V formula. This research used Educational Design Research type with Plomp as the development model. The average value of Aikens' V obtained is 0.892 for content validity, 0.896 for construct validity and 0.893 for expert validity, so that this e-module is stated to include category learning media that is already valid to be used during the learning process.